The Southwest Archives at Nuzi - Morrison, Martha A.
The Family of Taya – of Ṣupr-Adad – Taya son of Arim-matka — The Family of Šerta-ma-ilu – of Šellapai – of Tamar-tae – Paikku son of Аriḫ-ḫаrра – Puhiya son of Maši – Artaya son of Pui-tae – The School Texts – Miscellaneous Texts – Reconstructing the Southwest Archives – The People and the Character of the SW Archives. Appendix: Provenances of Tablets in the SW Area